Analysis of antioxidant response in pomelo fruitlets subjected to external injury stress: Significance of naringin biosynthesis. (October 2021) - Liu, Huifan; Liang, Churong; Ma, Lukai; Liu, Jianliang; Wang, Qin
Abstract: We simulated 2 types of external injuries in fruitlets—throwing and cutting with knife, and evaluated the degree of putrefaction. The external injury-induced toxicity was determined by observing changes in the spatial structure of the cells. Next, we determined the contents of lignin and total flavonoids, and the expression of phenylpropanoid pathway-related genes encoding enzymes that alleviate peroxidation toxicity. By measuring the content of naringin, we uncovered a non-enzymatic antioxidant mechanism that eliminates excessive reactive oxygen species (ROS) in fruitlets. We also determined that external injury triggers an increased activity of antioxidant enzymes. Overall, in fruitlets, external injuries activate naringin biosynthesis in response to stress. Highlights: Fruitlets showed external injury-induced toxicity following stress-induced treatments. The phenylpropane pathway was involved in alleviating peroxidation. The non-enzymatic antioxidant system contributed in alleviating peroxidation. External injury controlled the activity of antioxidant enzymes directly or indirectly.